1991
DOI: 10.1351/pac199163010071
|View full text |Cite
|
Sign up to set email alerts
|

Separation, identification, and quantification of carotenoids in fruits, vegetables and human plasma by high performance liquid chromatography

Abstract: Abstract-Separation, identification, and quantitation by high performance liquid chromatography of prominent carotenoids and carotenol fatty acid esters in various fruits and vegetables are reviewed. Examples of transformations of carotenoids as a result of food preparation are discussed. Recent developments in separation and identification of several carotenoids in human plasma are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(119 citation statements)
references
References 3 publications
6
108
0
5
Order By: Relevance
“…(ii) Khachik, Beecher, Goli, and Lusby (1991). 4 Method applied for the identification of the peak: (A) identification by comparison with the retention time and wavelengths of maximum absorption in the UV/Vis spectra of commercial standards; (B) identification by spectral interpretation of the wavelengths of maximum absorption in the UV/Vis spectra and comparison with wavelengths of maximum absorption reported in the literature (Chandrika, Jansz, & Warnasuriya, 2005;Lee, Castle, & Coates, 2001;Mendes-Pinto, Ferreira, Oliveira, & De Pinho, 2004;Taylor, Brackenridge, Vivier, & Oberholster, 2006); (C) identification by the order of chromatographic elution reported in the literature (Chandrika et al, 2005;Khachik et al, 1986;Lee et al, 2001;Mendes-Pinto et al, 2004;Taylor et al, 2006).…”
Section: Effect Of Defrosting Methods On Total and Individual Carotenmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) Khachik, Beecher, Goli, and Lusby (1991). 4 Method applied for the identification of the peak: (A) identification by comparison with the retention time and wavelengths of maximum absorption in the UV/Vis spectra of commercial standards; (B) identification by spectral interpretation of the wavelengths of maximum absorption in the UV/Vis spectra and comparison with wavelengths of maximum absorption reported in the literature (Chandrika, Jansz, & Warnasuriya, 2005;Lee, Castle, & Coates, 2001;Mendes-Pinto, Ferreira, Oliveira, & De Pinho, 2004;Taylor, Brackenridge, Vivier, & Oberholster, 2006); (C) identification by the order of chromatographic elution reported in the literature (Chandrika et al, 2005;Khachik et al, 1986;Lee et al, 2001;Mendes-Pinto et al, 2004;Taylor et al, 2006).…”
Section: Effect Of Defrosting Methods On Total and Individual Carotenmentioning
confidence: 99%
“…3 Previamente reportado por (i) Khachik et al (1986). (ii) Khachik et al (1991). 4 Método aplicado para la identificación del pico: (A) identificación por comparación con el tiempo de retención y longitudes de onda de máxima absorción en el espectro de UV/Vis de estándares comerciales; (B) identificación por interpretación del espectro de longitudes de onda de máxima absorción en el espectro de UV/Vis y comparación con longitudes de onda de máxima absorción reportadas en la literatura (Chandrika et al, 2005;Lee et al, 2001;Mendes-Pinto et al, 2004;Taylor et al, 2006); (C) identificación por el orden de elución cromatográfica reportado en la literatura (Chandrika et al, 2005;Khachik et al, 1986;Lee et al, 2001;Mendes-Pinto et al, 2004;Taylor et al, 2006).…”
Section: Effect Of Defrosting Methods On Total and Individual Carotenunclassified
“…As the methods for the determination of β-carotene, spectrophotometric (Biswas et al 2011;Schierle et al 2002) and chromatographic methods, both in normal and reversed phase, were used (Brabcova et al 2013;Burri et al 1997;Guedes De Pinho et al 2001;Hart and Scott 1995;Khachik et al 1991;Oliver and Palou 2000;RodriguezBernaldo De Quiros and Costa 2006). The chromatographic methods with the electrochemical detection were also described (Ferruzzi et al 1998;Murata et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Despite this, only 14 of these dietary carotenoids may be absorbed, modified, and/or used by the human body, 34 and yet only MZ, L, and Z are found at the macula, reflecting an exquisite degree of biological selectivity, which is unlikely to be accidental in design. 35 Studies have shown that L and Z are plentiful in many foodstuffs typical of a western diet (eg, spinach, kale, corn, and egg products).…”
Section: Origin Of the Macular Carotenoidsmentioning
confidence: 99%